TRANSLOG (Learning About Transportation And Logistic Maritim) : Media Pembelajaran Berbasis Tik-Tok - Andra Ahmad Fauzan; Taufiqurrahman Baaqir; Shania Amelia Dewi; Shaqnas Zetalia (Universitas Veteran Bangun Nusantara, 2022)
The use of TikTok-based learning media as an interesting and effective alternative in facilitating student learning. In education, learning that still uses demonstrative methods such as oral delivery of material can be boring and reduce interest in learning. Therefore, it is necessary to make modifications in learning strategies so that students can more easily understand the material through digital media. Keywords: Learning Media, Types of Learning Media, TikTok-Based Learning Media. In the context of learning, TikTok can be used as an interesting and effective learning medium. The advantages of using TikTok as a learning medium include flexibility, accessibility, a variety of content topics, easy repetition, and interactivity. Through the TikTok application, learners' skills in listening, reading, writing, and arithmetic can be developed. The research method used in this journal is a quantitative method that uses an approach with the calculation of numbers. This method involves observation and interviews as data sources. Observations were made on loading and unloading activities at the port, while interviews were conducted with related parties. The results and discussion of this journal show that the use of TikTok-based learning media can improve the quality of learning, especially in terms of selecting learning materials that are practical, innovative, and easy to understand. Digital learning environments, including the use of TikTok, can enhance interactive and engaging learning. TikTok-based learning about logistics transportation can be an interesting and effective alternative in helping students understand the topic.